Diversity of the diatom genus Fragilariopsis in the Argentine Sea and Antarctic waters: Morphology, distribution and abundance - Cefarelli, Adrián Oscar (2010)
Fragilariopsis species composition and abundance from the Argentine Sea and Antarctic waters were analyzed using light and electron microscopy. Twelve species (F. curta, F. cylindrus, F. kerguelensis, F. nana, F. obliquecostata, F. peragallii, F. pseudonana, F. rhombica, F. ritscheri, F. separanda, F. sublinearis and F. vanheurckii) are described and compared with samples from the Frenguelli Collection, Museo de La Plata, Argentina. F. peragallii was examined for the first time using electron microscopy, and F. pseudonana was recorded for the first time in Argentinean shelf waters. New information on the girdle view is included, except for the species F. curta, F. cylindrus and F. nana, for which information already existed. In the Argentine Sea, F. pseudonana was the most abundant Fragilariopsis species, and in Antarctic waters, F. curta was most abundant. Of the twelve species of Fragilariopsis documented, four occurred in the Argentine Sea, nine in the Drake Passage and twelve in the Weddell Sea. F. curta, F. kerguelensis, F. pseudonana and F. rhombica were present everywhere.